Resonance Raman studies of sterically hindered cyanomet "strapped" hemes. Effects of ligand distortion and base tension on iron-carbon bond. - Tanaka, T. (The Biophysical Society, 1987)
We report resonance Raman studies of the iron-carbon bond stretching vibrations, nu(Fe-CN), in sterically hindered and unhindered heme (FeIII)-CN- complexes. The sterically hindred "strapped hemes" are equipped with a covalently linked 13-, 14-, or 15-atom hydrocarbon chain across one face of the heme; these are called FeSP-13, FeSP-14, and FeSP-15, respectively. These straps would presumably exert a sideway shearing strain to force the linear ligands (e.g., CN- and CO) to be tilted and/or bent. The shorter the chain length, the weaker the ligand binding affinity because of a greater steric hindrance. This study reveals that the nu(Fe-CN) frequency decreases as the chain length is decreased, in contrast with the CO complexes, where the nu(Fe-CO) frequency increases as the chain length is decreased. For the heme-CN- complexes (with N-methylimidazole as a base), the nu(Fe-CN) frequencies are: heme 5 (unhindered), 451 cm-1; FeSP-15, 447 cm-1; FeSP-14, 447 cm-1; FeSP-13, 445 cm-1. For the heme-CO complexes (with N-methylimidazole as a base), the nu(Fe-CO) frequencies are: heme 5, 495 cm-1; FeSP-15, 509 cm-1; FeSP-14, 512 cm-1; FeSP-13, 514 cm-1 (Yu, N.-T., E. A. Kerr, B. Ward, and C. K. Chang, 1983, Biochemistry, 22:4534-4540). We have also studied the cyanide complexes with three different bases (pyridine, N-methylimidazole and 1,2-dimethylimidazole), and found that the trans-effect of cyanide complex is different from that of CO complexes. The tension on Fe"'-base bond weakens the Fe"'-CN- bond, whereas the tension on Fe"-base bond strengthens the Fe"-CO bond. The origin of these differences may be attributed to different extents of the d7r(Fe)- wr*(ligand) back bonding between the CN- and CO heme complexes. The Fe-C-N bending vibrations in these cyanomet strapped hemes are not resonance-enhanced, although this bending mode has been detected at -410 cm-' via Soret excitation in cyanometinsect hemoglobins. It is suggested that the orientation of the tilted Fe-C-N unit may be important in determining the overlap between CN and porphyrin 7r* orbitals, which provide coupling of the Fe-C-N bending mode with the resonant Soret (r-7r*) transition.